Pengelolaan Gangguan Persepsi Sensori Dengan Aktivitas Terjadwal Spiritual Dzikir Pada Pasien Halusinasi Pendengaran Di RSJ Prof. Dr. Soerojo Magelang: Management of Sensory Perception Disorders with Scheduled Spiritual Dhikr Activities in Auditory Hallucination Patients at Prof. Dr. Soerojo Mental Hospital, Magelang - Dhani, Rizky; Susilo, Tri (Jurnal Abdi Keperawatan dan Kedokteran, 2025)
Auditory hallucination is a core symptom of sensory perception disorder in schizophrenia patients, often impairing behavior and quality of life. One promising non-pharmacological intervention is scheduled spiritual dhikr (remembrance), believed to help patients relax and divert attention from hallucinatory stimuli. This study aims to examine the effect of scheduled dhikr therapy on the ability to control auditory hallucinations in patients with schizophrenia. This study applied a case study design using a psychiatric nursing process approach. The subject was a schizophrenia patient with auditory hallucinations at Prof. Dr. Soerojo Mental Hospital Magelang. The intervention involved scheduled dhikr activities conducted twice daily for three consecutive days (15–20 minutes per session), accompanied by behavioral observation and nursing documentation. After three days of therapy, there was a significant reduction in both the frequency and intensity of auditory hallucinations. The patient was able to perform dhikr independently, felt calmer, and showed improvements in self-control and social participation. These findings indicate that dhikr therapy is an effective spirituality-based nursing intervention for managing auditory hallucinations. It is recommended as a routine component of psychiatric nursing care to enhance patients' adaptation and quality of life.